POTENSIAL PELANGGARAN HUKUM PERSAINGAN PADA TATA NIAGA GULA - Ari Purwadi (Perspektif, 2004)
As a public policy instruments, implementation of sugar import commerce system should subject to fulfilling society needs especially customers, such as sugar cane farmers and sugar factories. The potential law violent towards cartel and oligopoly is based on "rule of reason" prohibition so that there is an act in accordance to elements of new related paragraphs when has been proven having negative effects.